The limits of performance at high altitude - Kayser, Bengt (Acta Andina, 2025)
The intensity of maximum exercise involving a large muscle mass that an acclimatized lowlander can sustain at altitude is reduced compared to sea level. In fact, exercise is stopped before the appearance of biochemical signs of peripheral fatigue. One possible hypothesis to explain the reduction of classical biochemical signs of fatigue in the muscle after exhaustive exercise at high altitude could be that central fatigue, induced by a maximally stressed respiratory system, would possibly limit such exercise with large muscle groups before their full potential is elicited. It appears that in controlled laboratory conditions at 5050m the muscular apparatus by itself remains in good condition and in principle capable for work .This seems to be the case only when a small muscle mass is activated. Exhaustion time of dynamic fore arm work at the identical absolute (maximum) load is the same at sea level and altitude, and similar signs of peripheral muscle fatigue develop before exhaustion is reached. By contrast, for similar exhaustion time, the absolute maximum cycling load maintained at 5050m is -20% lower than at sea level. Furthermore, while exhaustion during leg exercise at sea level is accompanied both by biochemical and electromyographical signs of peripheral fatigue, this is not the case at high altitude. Thus, at altitude, central rather than peripheral fatigue limits exhaustive exercise carried out with large muscle groups. Such mechanism could, at least partially, explain the decreased accumulation of lactic acid in blood in acclimatized subjects during exhaustive exercise at high altitude ("’lactate paradox’) and may represent a possible strategy for preserving vital respiratory functions from failure at altitude. lndeed at high altitude, the diaphragmatic contribution to ventilation during exercise at the same relative load decreases with time. This seems to be due to diaphragmatic fatigue, which hypothetically may contribute to exercise limitation at high altitude, although other mechanisms, like decreasing oxygen availability at the level of the central nervous system, may also play a role in limiting the duration of exhaustive exercise in conditions of chronic hypobaric hypoxia.